Imaginative Faith: Apocalyptic, Science Fiction Theory, and Theology - McMahon, Christopher (Dialog, 2008)
Both pastors and academic theologians have struggled with the place of apocalyptic language and imagery within the modern worldview. Many have dismissed apocalyptic as escapist and have alleged that it is divorced from the political and social concerns at the heart of contemporary theology and practice. Yet, contemporary critical theorists have overcome similar suspicions about science-fiction and now embrace it as a unique vehicle for thinking about the ills and the promise of contemporary culture. This essay suggests that within contemporary critical theory one finds useful tools for reading and using apocalyptic language and imagery as a means for engaging a world threatened by sin and violence.